Analisis Kualitas Layanan Pencairan Dana Dengan Aplikasi Elektronik Surak Perintah Membayar Pada Kantor Pelayanan Perbendaharaan Negara Sidikalang - Nova Juliana Sianturi; Syafruddin Ritonga; Rudi Salam (Mahesa Research Center, 2023)
This study aims to determine the service quality of electronic fund disbursement of Payment Orders at the Sidikalang State Treasury Service Office and the factors that influence it. This study used descriptive qualitative method. Using interview data collection techniques, observation, documentation and data triangulation. The results of this study indicate that the quality of the electronic fund disbursement service with a Payment Order at the Sidikalang State Treasury Service Office has implemented the dimensions of Tangibility, Reliability, Responsiveness, Assurance and Empathy. There are indicators that have not gone according to the wishes of the work unit, including the inconvenience of the service area including the infrastructure for service support facilities that are outside the service room. Meanwhile, the factors that affect the quality of disbursement of funds with electronic payment orders are the competence of service officers who are not yet uniform, and service facilities and infrastructure supporting service facilities that are less comfortable. It is necessary to uniform the competence of service personnel by participating in education and training, technical guidance, quality control groups or e-learning, increasing the comfort of service facilities and infrastructure and proposing to application developers to carry out application maintenance outside working hours so that application users are not disturbed in carrying out the disbursement process fund.